Effects of dietary red yeast (Sporidiobolus pararoseus) on production performance and egg quality of laying hens - Tapingkae W. (2017)
© 2017 Blackwell Verlag GmbH. The purpose of this study was to evaluate the effect of dietary red yeast (Sporidiobolus pararoseus) on production performance and egg quality of laying hens. A total of 200 Esa Brown laying hens (23 weeks of age) were allocated equally to negative control group (no yeast supplement); positive control group (2 g/kg of Saccharomyces cerevisiae); 0.5, 1, 2 g/kg red yeast respectively. The experiment was lasted for 12 weeks. Feed intake, hen-day egg production and egg weight were not different between control and supplemented groups. However, yeast-supplemented groups were significantly improved feed efficiency (p < .05). Incremental levels of red yeast increased the colour score of egg yolk (p < .05). The cholesterol and triglyceride of serum and yolk were significantly (p < .05) lower in the laying hens fed dietary administration red yeast compared to the control diet; however, no significant (p > .05) differences among yeast-supplemented groups were observed. The hepatic hydroxymethylglutaryl-coenzymeA (HMG-CoA) reductase activity was significantly lower (p < .05) in the 2 g/kg red yeast-supplemented group compared to the control and other red yeast-supplemented groups. Concentrations of caecal short-chain fatty acids was increased (p < .05) in laying hens fed 1 and 2 g/kg red yeast as compared to the control group. Dietary administration of 2 g/kg red yeast (S. pararoceus) significantly improved egg yolk colour, decrease serum and egg yolk cholesterol levels.